2022
DOI: 10.21203/rs.3.rs-1831482/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FinTech and CO2 Emission: Evidence from (Top 7) Mobile Money Economies in Africa

Abstract: Financial technology has evolved from a mediation role into an established sub-market within the financial ecosystem, gaining a superior advantage over the traditional financial system. Therefore, to ascertain if this advantage extends to protecting our environment, this study estimates the relationship between financial technology and carbon emission from the top seven (7) mobile money economies in sub-Saharan Africa. A balanced panel dataset from 2009 to 2020 is employed and estimated with the FMOLS estimato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Extending the literature to environmental pollution and Fintech, we notice that most studies have shown that Fintech can reduce environmental pollution and promote sustainable development [ 25 , 26 , 27 ]. In terms of greenhouse gases, some researchers have found that the development of Fintech can significantly reduce carbon dioxide emissions [ 28 , 29 , 30 ]. However, to date, little is known about the green attributes of Fintech [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extending the literature to environmental pollution and Fintech, we notice that most studies have shown that Fintech can reduce environmental pollution and promote sustainable development [ 25 , 26 , 27 ]. In terms of greenhouse gases, some researchers have found that the development of Fintech can significantly reduce carbon dioxide emissions [ 28 , 29 , 30 ]. However, to date, little is known about the green attributes of Fintech [ 25 ].…”
Section: Introductionmentioning
confidence: 99%